Influence of socio demographic factors on noncompliance among patients treated under RNTCP in a rural tuberculosis unit in Karimnagar district - Sairam, Amarvadhi; Guthi, Visweswara Rao; Prasad Sarma, M. M. V (International Journal Of Community Medicine And Public Health, 2017)
Background: Tuberculosis (TB) remains the number one killer infectious disease affecting adults in developing countries. The 1990 World Health Organization (WHO) report on the global burden of disease ranked TB as the seventh most morbidity-causing disease in the world, and expected it to continue in the same position up to 2020. The objective of this study is to evaluate the socio-demographic factors leading to non-compliance. Methods: The present study is case control study conducted to evaluate socio-demographic characteristics factors for non-compliance among patients treated under RNTCP in a rural tuberculosis unit in Karimnagar District. Among the 394 defaulters, 77 were not available at the address given to the TU during visits for sampling, 15 were not willing to participate and 2 patients were unable to communicate. 300 TB cases who have completed the treatment were taken as controls. Results: Age wise distribution of sample respondents is shown in above table. Most of the respondents 241 (40.2%) belonged to the age group of 31-40 years followed by 136 (22.7%) between age 41-50 years. 398 (66.3%) of them were male and 202 (33.7%) were female among the studied population. majority of the studied sample belonged to rural area 539 (89.8%) as compared to urban area 61 (10.2%). Conclusions: Increasing age with respondents above 40 years were likely to be non-compliant, living in a rural area, having migrated and belonging to low socio-economic status were also significant factors. Living in a nuclear family was also significant due to the lack of familial support. Patients who were tobacco users and consumers of alcohol were likely to be non-compliant. Families with multiple members suffering from TB were likely to have non-compliant patients.